The witch of Maracoor : a novel - Maguire, Gregory (Maguire, Gregory. Another day, 2023)
"Following a confrontation with her reclusive great-grandfather, the one-time Wizard of Oz, Rainary Ko--the granddaughter of Oz's Wicked Witch of the West--has re-upped in a mission to settle a few scores and right a wrong or two. Her memory and her passions reviving, Rain turns her gaze back to her native Oz. Though the Grimmerie, which she had cast into the sea, retains its arcane power over her, the lover she left behind in Oz proves no less haunting. Traveling companions and arrivistes can befuddle a young witch coming into her own, but Rain marshals a steely determination to stare her troubles in the eye and see who blinks first"--